Sarkofagus Samosir: Kreativitas Lokal Masyarakat Samosir - Taufiqurrahman Setiawan (Berkala Arkeologi Sangkhakala, 2009)
AbstractOne of the megalithic culture is sarcophagus. It appeared in someplace in Indonesia, such as Sulawesi, Nusa Tenggara, Bali, and also Sumatera. All has same function, as a sarcophagus, yet each has spescial characteristic.